Development of Teaching Materials on PLSV Using Scientific and Contextual Approach to Improve Mathematics Communication Ability and Self Confidence - Novi Ratna Dewi; Wahyu Hidayat; Euis Eti Rohaeti ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
Development of teaching materials on PLSV material using combination of scientific and contextual approach to improve mathematical communication ability and self confidence to seventh grade junior high school students. The purpose of this research and development is to obtain a design for developing  mathematical teaching materials in the form of lesson plans and worksheet with combination of scientific and contextual approaches to PLSV material for smpn 3 cipeundeuythis study also aims to test the level of validity, practicality, and effectiveness of teaching materials with a combination of scientific and contextual approaches to PLSV material. This research is a development research. The results showed that based on the assessment of material experts and mathematics teachers, the teaching materials developed had very valid criteria with an average total score of 190.33 for lesson plans and 297.5 for worksheets. Based on the results of filling out questions on communication skills and student responses questionnaires about self-confidence, there has been a significant increase. So it can be concluded that with the development of teaching materials by combining scientific and contextual approaches with the results of filling out observations of the implementation of learning and the results of evaluating learning outcomes, it can be concluded that the teaching materials developed have a very good level of effectiveness with the percentage of learning implementation of 94.87% and the percentage of completeness students to 95%.